Hubungan Model Kepercayaan Kesehatan (Health Belief Model) dengan Kepatuhan Minum Obat pada Pasien Hipertensi - Laili, Nurul; Aini, Efa Nur; Rahmayanti, Putri (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2023)
Introduction: One way to treat hypertension is taking medication. Adherence in carrying out therapy (taking medication) requires a perception or health belief model (Health Belief Model) to improve the quality of life. Objective: The aim of this study was to determine the relationship between the health belief model and medication adherence in hypertensive patients. Methods: Correlation Study research design with a Cross Sectional approach. The sampling technique is Purposive Sampling, the sample size is 57 respondents. The research instrument used the Health Belief Model and MMAS-8 questionnaire, Spearman Rho statistical test with a significance level of 0.05. Results: Analysis with the Spearman Rho statistical test obtained a p-value of 0.000 and an error rate of ? = 0.05 (0.000 <0.05) meaning that there is a relationship between the health belief model and medication adherence in hypertensive patients who have a positive relationship with strong category relationship strength (r = 0.791). Conclusions: Factors that influence the positive relationship include long suffering from hypertension and routine control. The higher the Health Belief Model in individuals, the higher the adherence to taking medication